EUFEMISME PENERJEMAHAN UNGKAPAN SEKSUAL NOVEL “SEPERTI DENDAM, RINDU HARUS DIBAYAR TUNTAS” KE DALAM BAHASA INGGRIS - Putri Sutaji, Tirta Ningtyas Alifia; Suray Agung Nugroho (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Euphemisms are often used in literary works The study aims to analyze the euphemistic form of sexuality expression in the translation of Eka Kurniawan's novel